The Influence of Self-Regulated Learning on Academic Achievement: A Cognitive-Behavioral Perspective - Nurul Hidayati; William Thompson (Innovative Journal of Educational Research and Insights, 2025)
This research investigates the influence of Self-Regulated Learning (SRL) on academic achievement through a cognitive-behavioral lens. SRL is recognized as a pivotal skill that enables learners to actively manage their learning processes, including setting goals, monitoring progress, and applying self-reflective strategies. The study adopts a quantitative correlational approach to examine how students' SRL competencies relate to their academic outcomes. The findings demonstrate a significant positive correlation between SRL and academic performance, suggesting that students with stronger self-regulation tend to achieve higher academic success. These results reinforce the cognitive-behavioral perspective, highlighting the importance of self-regulation in fostering effective learning behaviors. The study provides valuable implications for educational practice, particularly in designing programs aimed at enhancing students' SRL skills to boost academic achievement.